Integration of Virtual Care in the Audiology Service and Beyond. - Worthington, Darrin (American Journal of Audiology, 2025)
Purpose: This clinical focus article examines the history and evolution of telehealth, emphasizing its technological advancements, integration into health care systems, and the transformative impact of the COVID-19 pandemic on telehealth utilization in the United States, within the private sector and the Veterans Health Administration (VHA). Particular attention is given to the integration of audiology within telehealth, highlighting how the growth and use of teleaudiology services within the VHA have expanded access to this specialized care for Veterans. It aims to clarify how telehealth, including teleaudiology, has been established as a critical modality for enhancing health care access and delivery to Veterans. Conclusions: The historical context reveals that, while telehealth has roots tracing back to the American Civil War or earlier, the COVID-19 pandemic catalyzed an unprecedented surge in adoption and integration of telehealth services in both the private sector and the VHA. The data indicate a significant increase in telehealth encounters and patient satisfaction before, during, and after the COVID-19 pandemic, reinforcing its role as a complementary modality alongside traditional in-person care. Challenges such as regulatory barriers and digital access disparities continue to exist, yet ongoing efforts to embed telehealth training in health care education and to foster technological innovation signal a promising future for telehealth. As the health care landscape evolves, telehealth is poised to remain an integral component of patient-centered care.